PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA DI KANTOR SEKRETARIAT DPRD KABUPATEN KEPULAUAN MERANTI - Sari Julita; Indra Prasetyo; Woro Utari (BBM (Buletin Bisnis & Manajemen), 2022)
The purpose of this study was to determine and describe the work environment, compensation, job satisfaction and employee performance in the Secretariat Office of the DPRD Meranti Islands District Court, Law and Aspiration Data Processing and to determine and analyze the influence between work environment and compensation on employee performance through satisfaction. work. The population and sample used in the study were 37 employees with a total sampling technique. Data collection through questionnaires. Data processing in this study using SPSS Statistics version 25. The analysis technique uses path analysis. The results showed that the work environment, compensation, job satisfaction and employee performance could be categorized quite well. Work environment and compensation have a significant effect on job satisfaction. Work environment and job satisfaction have a significant effect on employee performance while compensation has no significant effect on employee performance. The work environment has a significant effect on employee performance through job satisfaction, while compensation has no significant effect on employee performance through job satisfaction